2003
DOI: 10.1074/jbc.m209250200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Archaeal Transcriptional Regulator of Heat Shock Response

Abstract: Archaea have a eukaryotic type of transcriptional machinery containing homologues of the transcription factors TATA-binding protein (TBP) and TFIIB (TFB) and a pol II type of RNA polymerase, whereas transcriptional regulators identified in archaeal genomes have bacterial counterparts. We describe here a novel regulator of heat shock response, Phr, from the hyperthermophilic archaeon Pyrococcus furiosus that is conserved among Euryarchaeota. The protein specifically inhibited cellfree transcription of its own g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 31 publications
1
95
0
Order By: Relevance
“…Our KMnO 4 footprints at 70°C (Fig. 5A) demonstrated that TFE leads to an increased complex stability by promoting DNA melting similar to the properties reported for eukaryotic TFIIE␣ (12,24,42). The roles of EЈ and TFE in open complex formation were better resolved when initiation by the Pyrococcus core enzyme was analyzed at 60°C.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our KMnO 4 footprints at 70°C (Fig. 5A) demonstrated that TFE leads to an increased complex stability by promoting DNA melting similar to the properties reported for eukaryotic TFIIE␣ (12,24,42). The roles of EЈ and TFE in open complex formation were better resolved when initiation by the Pyrococcus core enzyme was analyzed at 60°C.…”
Section: Discussionmentioning
confidence: 59%
“…The ⌬EЈF RNAP is therefore also designated as core enzyme here. The most active fractions of the core enzyme were eluting later (fractions [23][24][25][26] indicating that the lower activity of fractions 19 -21 containing higher amounts of RNAP (see SDS-PAGE of RNAP fractions in Fig. 2B) was not caused by a lower content of subunits EЈ and F in these fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10). Apart from such genome-based approaches targeting FFRPs, a small number of archaeal transcription factors were experimentally identified in the past few years by other groups while focusing mainly on biological phenomena such as heat-shock responses 28) and metabolic changes induced by particular nutrients. 29) The aim of this paper Apparent similarity between the amino acid sequences of FL-FFRPs is low.…”
Section: )-27)mentioning
confidence: 99%
“…E. coli Lrp, has been reported. 31) In this study five archaeal transcription factors, Phr, 28) TrmB, 29) GvpE, 32) MDR1 33) and NrpR, 34) are analyzed, which were almost all the experimentally identified transcription factors I was able to find by searching literature. These form a random selection of archaeal transcription factors, for none of which the authors of the original papers claimed significant similarity to FFRPs.…”
Section: )mentioning
confidence: 99%